“I want to die many times if this is true” (Plat., Ap., 41b). Socrates, Palamedes, and the rhetorical exercises in the horizon of the Socratic dialogue (Revista Archai, 2021)
The figure of Socrates divides the history of Western thought into two parts. It inaugurates a model of philosophy that shaped all subsequent tradition with the sole force of its influence and the totemic aura from his tragic death. There were many accounts of what happened, but none of them overshadowed Plato's Apology of Socrates as a fundamental text for entering into the details of the trial and sentence. In this context, the opacity of this text is rarely taken into account. It seems to be a testimonial document, a quasi-stenographic version of the process, but it is not. In fact, we are interested in referring to a fact that has been noted but not entirely dimensioned: Plato's Apology of Socrates presents similarities impossible to attribute to mere chance with Gorgias’ Apology of Palamedes. Why does this Platonic text present curious intertextual relationships with a rhetorical exercise based on mythical figures in the climate of the promotion of rhetoric? We will try to answer this question appealing to its link with the origin of the Socratic dialogue.